Matching Local Food Messages to Consumer Motivators: An Experiment Comparing the Effects of Differently Framed Messages - Katie M Abrams; Catharine Soukup (Journal of Applied Communications, 2017)
Past research suggests the local food movement provides economic and social benefits to consumers and producers alike. These benefits might account for the significant increase in local food sales. Despite its increasing popularity, further communications research is needed since a dominant messaging strategy does not currently exist to advance the local food movement. Food quality, healthfulness, and support of local farmers were previously empirically identified as motivating factors to purchase local food; however, they had not been tested comparatively for effectiveness. Based in framing theory and the theory of planned behavior, we sought to test if brief messages framed to target these motivations could bolster cognitive antecedents known to predict behavioral intent to purchase local foods. The experiment was conducted with 408 study participants recruited from general education courses at a large, public university in Colorado. Results showed no difference between the message frames and no effect (compared to the control group message) on any of the measures. These findings suggest consumers are becoming increasingly savvy when it comes to local food advertisements and probably have developed a relatively stable attitude toward local food. We suggest that future research might yield deeper explanatory results if pre-existing attitudes and participants’ elaboration likelihood are considered. Our findings also suggest local food marketers should consider communication strategies and tactics that provide richer information/arguments to consumers; brief ads are likely insufficient.
Keywords: Local food; framing theory; theory of planned behavior; message effects